Long-term cortisol stress response in depression and comorbid anxiety is linked with reduced N-acetylaspartate in the anterior cingulate cortex. (2nd January 2023) - Bonnekoh, Linda M.; Seidenbecher, Stephanie; Knigge, Katrin; Hünecke, Anne-Kathrin; Metzger, Coraline D.; Tempelmann, Claus; Kanowski, Martin; Kaufmann, Jörn; Meyer-Lotz, Gabriela; Schlaaff, Konstantin; Dobrowolny, Henrik; Tozzi, Leonardo; et al.
Abstract: Objectives: Major Depression (MDD) and anxiety disorders are stress-related disorders that share pathophysiological mechanisms. There is evidence for alterations of glutamate-glutamine, N-acetylaspartate (NAA) and GABA in the anterior cingulate cortex (ACC), a stress-sensitive region affected by hypothalamic-pituitary-adrenal axis (HPA). The aim was to investigate metabolic alterations in the ACC and whether hair cortisol, current stress or early life adversity predict them. Methods: We investigated 22 patients with MDD and comorbid anxiety disorder and 23 healthy controls. Proton magnetic resonance spectroscopy was performed with voxels placed in pregenual (pg) and dorsal (d) ACC in 3 T. Analysis of hair cortisol was performed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: The N-acetylaspartate/Creatin ratio (NAA/Cr) was reduced in patients in both pgACC ( p = .040) and dACC ( p = .016). A significant interactive effect of diagnosis and cortisol on both pg-NAA/Cr (F = 5.00, p = .033) and d-NAA/Cr (F = 7.86, p = .009) was detected, whereby in controls cortisol was positively correlated with d-NAA/Cr (r = 0.61, p = .004). Conclusions: Our results suggest a relationship between NAA metabolism in ACC and HPA axis activity as represented by long-term cortisol output.